Innovations in energy storage - L. R. Mukhametova; I. G. Akhmetova; W. Strielkowski (Известия высших учебных заведений: Проблемы энергетики)
The development of energy storage and storage systems is becoming a potential method for solving the problems of the global energy system. However, there are technical and non-technical barriers to the widespread distribution of energy storage devices. In this regard, it is necessary to identify innovative processes, mechanisms and systems that allow developments in the field of energy storage to contribute to solving the problems of the energy system, as well as to ensure industrial growth at the expense of companies engaged in the development of technologies. This article discusses current advances and trends in energy storage innovation. The scientific novelty of the article consists in a comprehensive review of the current state of affairs in this area and the determination of the main directions of development.